Pengaruh Pendapatan Asli Desa, Dana Desa dan Alokasi Dana Desa Terhadap Belanja Desa di Provinsi Sumatera Selatan - Renaldy, Dwingki; Pangaribuan, Sonang Pestaria; Oktariyani, Amanda (Akuntansi dan Manajemen, 2024)
This study aims to determine the Impact of Village Original Income, Village Funds, and Village Fund Allocation on Village Expenditure in South Sumatra Province. The research is specifically focused on the regencies/cities within South Sumatra Province. The study utilizes secondary data obtained from the revenue and expenditure realization reports of village governments in South Sumatra Province. The sample consists of 10 regencies/cities with a total of 40 observation data points from the village government revenue and expenditure realization reports in South Sumatra Province. The data analysis technique employed is multiple linear regression using SPSS software version 26. The results indicate that simultaneously, Village Original Income, Village Funds, and Village Fund Allocation have a positive effect on Village Expenditure. Furthermore, partially, Village Original Income does not affect Village Expenditure, whereas Village Funds and Village Fund Allocation positively affect Village Expenditure. The findings emphasize the importance of optimizing the management of Village Funds and Village Fund Allocation to enhance productive village expenditures, while strategies to increase the contribution of Village Original Income need further development.